Smart Safety Hikers Application - Lim Yi Chen,; Hamid Ali, Firkhan Ali (Applied Information Technology And Computer Science, 2023)
The number of people who go missing due to mountain climbing is increasing every year. A mobile-based Emergency Distress Signal application was developed to help hikers can seek help when they lost their direction or do not reach their destination in the stipulated time. The application can send distress signals including the user’s longitude and latitude and the user’s alert message to team volunteers when they miss the direction. Other than that, users can also view the emergency note that will lead them to solve the problem accordingly such as injured and lost direction. The Prototype Model technique was utilized to create this application. The actions carried out for the creation of this application include identifying the issue statement, objectives, and application requirements, designing the application interface, and creating the database. The Java programming language and Android Studio were used to create this application. The database is built using the Firebase platform. It is hoped that this application would be created effectively and be able to assist those missing hikers getting rescued by volunteer teams.